Perancangan Sistem Pendukung Keputusan Beasiswa Menggunakan Metode SAW Di Universitas Advent Indonesia - Elmor Benedict Wagiu; Raymond Matheus (TeIKa, 2017)
Scholarship decision support systems conducted by Universitas Advent Indonesia still use manual processes. Manual Decision support systems for scholarships have problems that require a long time, consumes the mind and energy to choose students who want to get a scholarship, and have a fairly large error rate. The research objectives are (1) making an application that is useful for assisting in the process of supporting scholarship decisions at Universitas Advent Indonesia and (2) facilitating the ranking process of prospective students who receive scholarships at the Universitas Advent Indonesia more efficiently. This research uses SDLC (System Development Life Cycle) research methodology and also uses the interview method to the related parties of the scholarship to obtain the required scholarship criteria data. The results obtained from the construction of a scholarship decision support system are the system has been able to process the ranking and display the selected data.